Association between mortality and incidence rates of coronary heart disease and stroke: The Japan Public Health Center-based prospective (JPHC) study. (1st November 2016) - Saito, Isao; Yamagishi, Kazumasa; Kokubo, Yoshihiro; Yatsuya, Hiroshi; Iso, Hiroyasu; Sawada, Norie; Inoue, Manami; Tsugane, Shoichiro
Abstract: Background: It is essential to have information on incidence rates to estimate the burden of cardiovascular diseases (CVD); however, it is not clear whether mortality measurements are eligible for incidence estimations. Methods: We performed eight cohort studies from 1990 to 2010 in Japan, which consisted of total 94, 657 residents aged 40–59 years who were followed-up for a median of 18.5 years. Incidence and mortality rates for coronary heart disease (CHD) and stroke events were ascertained. Sex-specified incidence rates were regressed to the mortality rates, adjusting for differences in community and age group. Further, incidence-to-mortality rate ratios were estimated using the Poisson regression with random intercepts. Results: CHD or stroke mortality rates were highly associated with incidence rates in communities. Incidence-to-mortality rate ratios were 2.06 (95% confidence interval, 1.56–2.73) in men and 1.41 (1.01–1.95) in women for CHD; and 3.99 (3.32–4.80) in men and 4.44 (3.73–5.29) in women for stroke. There were no significant geographical variations in the ratio among the 8 areas. Conclusions: We determined that it is possible to estimate CHD and stroke occurrences in the population from their mortality rates reported in vital statistics. Accordingly, we should pay attention to the communities in which mortality rates due to CHD or stroke reported in vital statistics are higher, and promote CVD prevention positively.